Sustainable synthesis of nano CuO from electronic waste (E-waste) cable: Evaluation of crystallite size via Scherrer equation, Williamson-Hall plot, Halder- Wagner model, Monshi-Scherrer model, size-strain plot - Md. Sahadat Hossain; Samina Ahmed (Results in Engineering, 2023)
Electronic waste (E-waste) is going to be one of the most hazardous materials for a sustainable environment in the technologically advanced era. In this research, waste electric cable was taken for efficient production of CuO using an easy and simple way. The synthesized product, CuO, was confirmed by the X-ray diffraction (XRD) data, and optical bandgap energy was also estimated. Various crystallographic parameters such as lattice parameters, the volume of unit cell, relative intensity, and preference growth were estimated from XRD data. Scherrer equation, Williamson-Hall plot (Uniform Deformation Model (UDM), Uniform Stress Deformation Model (USDM), Uniform Deformation Energy Density Model (UDEDM)), Halder-Wagner Model, Monshi-Scherrer Model, and Size- Strain plot were employed to calculate crystallite size and few models also exerted stress, strain and energy density. The estimated range of crystallite size was from 7 to 14 nm, strain from 5 × 10−4 to 1.5 × 10−3, stress of 1.0487 GPa, and energy density of 8.12 × 10−4 GPa using different model equations. The preference growth indicated that the (2 0 0) plane is the preferred direction for the synthesized conditions. FTIR spectrum and optical bandgap energy were also estimated for the synthesized products. The Rietveld refinement indicated that the synthesized product contained 99.524 % tenorite (CuO), and 0.476 % Cu2O phases.